Keputusan Mahkamah Konstitusi Tentang Pemungutan Suara UlangPemilihan Kepada Daerah Serentak 2020 Sebagai PerwujudanDemokrasi - Estiningrum; Wahyu Hariadi (Wijayakusuma Law Review, 2022)
The number of applications for re-voting (PSU) granted by the Constitutional Court (MK) in 16 regions in the2020 Simultaneous Regional Head Elections (Pilkada), this is the largest number since the 2015 simultaneousPilkada era. In 2015 there were 4 requests granted, year In 2017 there were 6 requests that were granted andin 2018 there were 5 requests that were granted. The purpose of this research is to analyze whether thedecision of the Constitutional Court regarding Re-Voting for the 2020 Simultaneous Regional Elections is amanifestation of democracy from people's sovereignty. The method used in this research is doctrinal legalresearch through statutory and case approaches. The success of the Regional Head Election (Pilkada) as aparameter of democracy does not lie in the presence or absence of Pilkada, but rather in the quality of theimplementation of the Pilkada itself. This means that regional elections are carried out in accordance withfour concepts, namely regional elections as a means of people's sovereignty, carried out in a liberal and fairmanner, carried out in the Unitary State of the Republic of Indonesia, and carried out based on Pancasila andthe 1945 Constitution. elections that have integrity, professionalism and accountability. Democratic Pilkadais a value mandated in Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning theElection of Governors, Regents and Mayors to Become Laws. Democratic values in their implementationsometimes do not materialize in their implementation, the Constitutional Court as the guardian of democracycan issue a decision to carry out a Re-Vote. Pilkada So that the re-voting is part of the embodiment ofdemocracy which must be carried out properly.